Analyzing Inner Conflict in “PRIDE.” Through Schema Theory and Metaphor - Lubis, Rafi Muhammad; Azahra, Naiya; Sinaga, Joyce Chardha; Siregar, Akbar Pangeran; Rangkuti, Rahmadsyah (Journal of English Language and Education, 2025)
Kendrick Lamar's 2017 song "PRIDE." from his album DAMN. goes with themes of internal chaos, pride, and regrets. Using a cognitive stylistic method, this study investigates how Lamar's metaphors influence listeners' perceptions and emotional comprehension. It answers two key queries: (1) Which schemas or mental models are activated in the brains of the listeners? and (2) How are complicated feelings like pride and shame expressed through Lamar's metaphors? Drawing on the song's official lyrics, the analysis is based on Schema Theory (Anderson, 1977) and Conceptual Metaphor Theory (Lakoff Johnson, 1980). By examining recurrent patterns of imagery, word choice, and narrative structures that correspond with experiences that are both cognitively and culturally recognizable, schemas may be found in the lyrics. For example, Lamar's use of chronological changes (“I was born like this”) and geographical oppositions (“sitting in silence”) to illustrate internal struggle activates schemas linked to memory, self-examination, and moral dualism. Metaphors like "empathy as sacrifice" and "pride as death" appeal to common conceptual frameworks in which empathy is linked to vulnerability or redemption and pride to destruction or collapse. Listeners are able to emotionally connect with the abstract problems Lamar offers because these metaphorical expressions suggest larger schemas regarding identity, morality, relationships, and spiritual tension.